Dietary fortification of crushed seeds of Bonium persicum on growth performance, apparent ileal digestibility and blood metabolites in broiler chicks during the starter phase. Issue 1 (1st January 2021) - Shuaib, Muhammad; Ullah, Nasr; Hafeez, Abdul; Khan, Najeeb Ullah; Alhidary, Ibrahim A.; Abelrahman, Mutassim M.; Albadani, Hani; Khan, Rifat Ullah
Abstract: The aim of the present study was to find the effect of crushed wild Cumin ( Bonium persicum ) seeds as a feed additive in broiler diet during the starter phase on growth performance, nutrient digestibility and blood metabolites in broilers. For this purpose, 360 day old chicks were randomly divided into four groups. One group was the control while other experimental groups were supplemented with crushed wild Cumin (WC) seeds in the feed at the rate of 0.5 (WC1), 1 (WC2) and 1.5 g/kg (WC3). Results indicated that feed intake was significantly lower ( p < .05) in WC1 and WC2 compared to WC3 and the control. Body weight was significantly ( p < .05) higher in WC1 compared to the WC2. Feed conversion ratio was significantly ( p < .05) lower in WC1 compared to the control. Percentage of crude fat, protein and calcium digestibility was significantly ( p < .05) higher in WC1 compared to the control. Similarly, low density lipoprotein, total cholesterol and triglycerides concentration was significantly ( p < .05) lower in WC1 and high density lipoprotein (HDL) cholesterol was significantly ( p < .05) improved . On the overall basis, wild Cumin seeds at the rate of 0.5 g/kg were comparatively better to improve the growth, gut digestibility of the nutrients and blood cholesterol profile in broiler during the starter phase. HIGHLIGHTS: Feed intake was lower in WC1 Weight gain was higher in WC1 Digestibility of nutrients was higher in WC1 Blood cholesterol was lower in WC1